The stargate conspiracy : revealing the truth behind extraterrestrial contact, military intelligence and the mysteries of ancient Egypt /: revealing the truth behind extraterrestrial contact, military intelligence and the mysteries of ancient Egypt. (2019) - Picknett, Lynn; Prince, Clive
No abstract available